Analisis Manajemen Pembelajaran Kesetaraan Paket C dalam Membentuk Karakter Siswa PKBM Insan Muwahid Garut - Suherman, Maman; H. Soro, Suharyanto; Yesino, Leonardus; Zuhri, Saepudin; Nurjanah, Ana (LP. Ma'arif Janggan Magetan, 2024)
Package C equivalency education (Non-formal Education) contributes positively to the formation of student character. The existence of non-formal education is officially recognized by the state. In other words, non-formal education can be used as one of the proofs that the person attended school and obtained a graduation certificate. This study aims to find the management of package C equivalency learning in shaping student character. The researcher used a qualitative research method with a case study approach. The sample in the study was selected purposively. The data collection method used observation, interview, and documentation study methods. The research activity was carried out in the 2024 academic year. The results of the study showed that effective learning management at PKBM Insan Muwahid created an inclusive learning environment and supported the development of student character. The role of teachers as teachers and role models is very significant in the formation of student character, especially through habits and examples applied in the learning process. In other words, the management of equivalency learning not only focuses on academic aspects, but also plays an important role in the development of students' moral and ethical values, which contribute to character.